Forming a Social structure in mobile opportunistic networks - Halikul, Lenando; Kartinah, Zen; Mohamad Nazim, Jambli; Thangaveloo, R. (IEEE, 2012)
In mobile opportunistic networks, the network topology is unpredictable and very dynamic. Thus, broadcast or flooding is the best way to disseminate information. However, this approach consumes a lot of resources and introduces a duplication problem. One way to overcome this problem is to understand the relationship between the mobile nodes to guide the information dissemination flow. In this paper, we introduce three different approaches to form a node social relationship based on the node frequency interactions. The methods are Social structure based on average frequency interactions, Social Structure based on Periodicity Frequency Interactions and Social Structure based on Sliding Window. The results show that it is possible to form a social structure based on the nodes frequency interactions with other nodes. The most suitable approach to represent the nodes social relationship in opportunistic networks is the social structure based on Sliding Window approach.